Peningkatan Hasil Belajar Siswa Kelas V SDN 011 Pulau Kedundung pada Mata Pelajaran IPA dengan Materi Sifat-Sifat Cahaya melalui Metode Percobaan - Rayanis, Rayanis (GERAM, 2017)
The research was motivated by the findings on Science learning process about light properties where there were only 50% students who passed the minimal mastery score. To improve the score, the experiment method was applied. The objective of this research was to improve students’ learning result in SD N 011 Pulau Kedundung grade V. This research was based on four steps of Classroom Action Research; planning, proceeding, observing, and reflecting. It was done in two cycles. The result of the research showed there was significant improvement in cycle 1 that 80% students passed the score and in cycle 2, 100% students passed. It can be concluded that the use of experiment method could improve students’ learning result SD N 011 Pulau Kedundung grade V in Science learning about light properties.